Analisis Strategi Pemasaran untuk Meningkatkan Daya Saing UMKM Keripik Pisang di Desa Ciherang Pondok - Amin, Ahmad Muladi; Rahmat, Faridudin Malikur (ALIF: Sharia Economics Journal, 2024)
The aim of this research is to determine marketing strategies to increase the competitiveness of Micro, Small and Medium Enterprises (MSMEs), especially in the banana chips business in Ciherang Pondok sub-district. The analysis method uses descriptive research methods with a qualitative approach carried out through observation, interviews and documentation. The research results show that banana chips MSMEs use E-marketingcommerce, so that product sales and skills can increase.  From the analysis carried out on banana chips industry products, a marketing strategy can be implemented as an effort to increase internal competitiveness. Apart from that, banana chips businesses also use a marketing mix. In this case, it shows that the product being sold is very attractive because the main ingredient is quality bananas and the place is comfortable, clean and hygienic, the price is relatively cheap and affordable as well as promotion by utilizing social media such as Facebook, Instagram and WhatsApp.